A positive electrode material and preparation method thereof, battery and application

A lithium iron phosphate-based electrode material with a coated layer of amino acid chelated titanium and diisobutylaluminum acetylacetonate complex addresses structural limitations, achieving high energy density and improved cycle stability through co-doping with carbon, nitrogen, and aluminum.

CN118825279BActive Publication Date: 2024-12-13HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310477.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Lithium iron phosphate cathode materials face challenges in achieving improved energy density, power performance, and low-temperature performance due to structural limitations and doping inefficiencies.

Method used

A positive electrode material is developed with a lithium iron phosphate core coated with a layer containing amino acid chelated titanium and diisobutylaluminum acetylacetonate complex, co-doped with carbon, nitrogen, and aluminum, forming strong chemical bonds to stabilize the structure and enhance conductivity.

Benefits of technology

The material exhibits high energy density, fast ion conduction, and improved cycle stability, with reduced internal resistance and enhanced charge/discharge rates, maintaining structural integrity during electrochemical processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825279B_ABST
    Figure CN118825279B_ABST
Patent Text Reader

Abstract

The present invention discloses a positive electrode material and a preparation method, a battery and an application thereof, and relates to the technical field of lithium batteries. A positive electrode material comprises a core and a coating layer; the core is lithium iron phosphate; the raw materials for preparing the coating layer include amino acid chelated titanium and diisobutylaluminum acetylacetonate complex; the raw materials for preparing amino acid chelated titanium include the following raw materials in molar fractions: 10 parts of amino acid, 20-50 parts of quaternary ammonium hydroxide salt, 3-8 parts of tetraalkyl titanate and 30-60 parts of ethanol. The positive electrode material prepared by the method has excellent electrochemical properties in terms of energy density, conductivity, charge and discharge efficiency and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to a positive electrode material and a preparation method thereof, a battery, and applications. Background Art

[0002] Lithium iron phosphate (LiFePO4) cathode material is a high-performance material for lithium-ion batteries. It is favored for its high safety, high cycle stability and low cost, but it also has the disadvantages of relatively low energy density and poor low-temperature performance.

[0003] Although the introduction of metal elements (such as manganese, cobalt, nickel, aluminum, titanium) or non-metallic elements (such as nitrogen, sulfur, fluorine) into lithium iron phosphate cathode materials can improve its conductivity and the diffusion rate of lithium ions to a certain extent, thereby enhancing the rapid charge and discharge capabilities of the battery, this method still faces many challenges in practical applications. The inherent structure of lithium iron phosphate limits the performance improvement effect brought by doping, resulting in the improved battery performance still failing to achieve the expected goal. Summary of the invention

[0004] The present invention overcomes the above technical problems. The present invention provides a positive electrode material and a preparation method thereof, a battery, and an application thereof. The positive electrode material of the present invention has good performance in at least one aspect, such as energy density, power performance, and cycle stability.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] A positive electrode material comprises a core and a coating layer;

[0007] The core is lithium iron phosphate;

[0008] The raw materials for preparing the coating layer include amino acid chelated titanium and diisobutylaluminum acetylacetonate complex (CAS No.: 24772-51-8);

[0009] The raw materials for preparing the amino acid chelated titanium include the following raw materials in molar proportions: 10 parts of amino acid, 20-50 parts of quaternary ammonium hydroxide salt, 3-8 parts of tetraalkyl titanate and 30-60 parts of ethanol.

[0010] The cathode material coating layer of the present invention uses amino acid chelated titanium and diisobutylaluminum acetylacetonate as raw materials to achieve co-doping of carbon, nitrogen, titanium and aluminum. This doping strategy not only significantly improves the cyclic stability of the material, but also effectively prevents structural transformation and lattice oxygen loss that may occur during the electrochemical process. Ti and Al co-doping further reduces the residual stress in the film and optimizes the structure of the material, which helps to maintain the structural integrity of the material during the charge and discharge process. The strong chemical bonds formed by Al and Ti with oxygen not only stabilize the structure of the material, but also alleviate the lithium ion (Li + ) disorder, thereby promoting fast ion conduction. Carbon and nitrogen doping further enhances the conductivity of the material. Nitrogen, as an electron donor, not only improves the conductivity but also increases the surface active sites by introducing local tension and structural defects in the material, which is crucial for improving the charge and discharge performance of the battery. In addition, nitrogen doping also helps to fix metal ions, which not only optimizes the microstructure and surface properties of the material, but also reduces the internal resistance, further improving the charge and discharge rate.

[0011] In the present invention, the amino acid is L-glutamic acid (CAS No.: 56-86-0) or L-arginine (CAS No.: 74-79-3).

[0012] In the present invention, the quaternary ammonium hydroxide salt is at least one of tetrabutylammonium hydroxide (CAS No.: 2052-49-5), tetraethylammonium hydroxide (CAS No.: 77-98-5) and dimethyldiethylammonium hydroxide (CAS No.: 95500-19-9).

[0013] In the present invention, the tetraalkyl titanate is tetrabutyl titanate (CAS No.: 5593-70-4) or tetraisopropyl titanate (CAS No.: 546-68-9).

[0014] In the present invention, the molar ratio of the amino acid chelated titanium to lithium iron phosphate is 1:6.5-7.5, preferably 1:6.8-7.1.

[0015] In the present invention, the molar ratio of the tetraalkyl titanate to the diisobutylaluminum acetylacetonate complex is 1:3-5, preferably 1:3.5-4.5.

[0016] In the present invention, the powder resistivity of the positive electrode material is 6.5-15 Ω·cm, preferably 6.8-8.71 Ω·cm, for example, 6.80 Ω·cm, 7.77 Ω·cm, 8.16 Ω·cm, 8.59 Ω·cm or 8.71 Ω·cm.

[0017] In the present invention, the specific surface area of ​​the positive electrode material is 8.5-15.5 m 2 / g, preferably 11.35~15.09 m 2 / g, for example, 11.35 m 2 / g, 11.98 m 2 / g, 12.03 m 2 / g, 13.64 m 2 / g or 15.09 m 2 / g.

[0018] In the present invention, the compaction density of the positive electrode material is 2.40-2.85 g / cm 3 , preferably 2.65~2.73 g / cm 3 , for example 2.65 g / cm 3 , 2.67 g / cm 3 , 2.70 g / cm 3 , 2.71 g / cm 3 or 2.73 g / cm 3 .

[0019] The present invention provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:

[0020] S1. Mixing an amino acid and a quaternary ammonium hydroxide salt in water to obtain a first solution;

[0021] S2. The tetraalkyl titanate is mixed in ethanol to obtain a second solution;

[0022] S3. adding the first solution dropwise to the second solution and mixing to obtain a precursor solution;

[0023] S4. The precursor solution is dried, sintered, crystallized, and crushed to obtain amino acid chelated titanium;

[0024] S5. Mix amino acid chelated titanium, diisobutylaluminum acetylacetonate complex and lithium iron phosphate, calcine and anneal to obtain a positive electrode material.

[0025] Among them, the tetraalkyl titanate after alcoholysis can react with amino acid under the action of quaternary ammonium hydroxide to form amino acid chelated titanium. The structure of amino acid chelated titanium is , wherein R is hydrogen or an alkyl group, and L is an amino acid.

[0026] In S1, the molar ratio of the amino acid to the water is 1:15-50.

[0027] In S2, the mixing temperature is 40-50°C.

[0028] In S2, the mixing time is 2 to 5 hours.

[0029] In S4, the drying temperature is 100-170°C.

[0030] In S4, the drying time is 2 to 8 hours.

[0031] In S4, the temperature of the sintering crystallization is 300-400°C.

[0032] In S4, the sintering crystallization time is 5 to 8 hours.

[0033] In S4, the particle size of the crushed material is D50=0.7~0.85 μm, preferably 0.75~0.79 μm.

[0034] In S5, the calcination time is 2 to 5 hours.

[0035] In S5, the calcination temperature is 700-900°C.

[0036] In S5, the annealing temperature is 500-600°C, preferably 500-530°C, for example 500°C.

[0037] In S5, the annealing temperature is maintained for 1 to 2.5 hours.

[0038] The present invention provides a battery, comprising a positive electrode, a separator, a negative electrode and an electrolyte, wherein the positive electrode plate comprises the positive electrode material mentioned above.

[0039] In the present invention, the capacity retention rate of the battery after 200 cycles at a 5.0C rate is 85.6-93.8%, preferably 86.5-88.3%.

[0040] In the present invention, the battery has a discharge capacity of 159.8-162.9 mAh / g at a 0.1C rate.

[0041] In the present invention, the battery has a discharge capacity of 151.9-153.7 mAh / g at a 1.0C rate.

[0042] In the present invention, the battery has a discharge capacity of 132.5-134.2 mAh / g at a rate of 5.0C.

[0043] Application of the positive electrode material prepared by the method for preparing the positive electrode material, the positive electrode material, and the battery in household appliances, electric bicycles, electric vehicles, electric trains, ships, satellites, or power grid energy storage systems.

[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] 1. The cathode material coating of the present invention is co-doped with carbon, nitrogen, titanium and aluminum using amino acid chelated titanium and diisobutylaluminum acetylacetonate complexes. This doping technology significantly improves the cyclic stability of the material and prevents structural changes and lattice oxygen loss during the electrochemical process. The strong chemical bonds between Al and Ti and oxygen stabilize the lithium iron phosphate structure, promote lithium ion conduction, and form fast ion conduction channels. Carbon and nitrogen doping improves electrical conductivity, and nitrogen as an electron donor increases structural defects and surface active sites. This doping reduces internal resistance and improves charge and discharge rates.

[0047] 2. The positive electrode material of the present invention has the characteristics of high energy density, high battery charge and discharge efficiency and excellent electrochemical reaction. The powder resistivity of the positive electrode material is 6.5-15 Ω·cm, and in some preferred embodiments is 6.8-8.71 Ω·cm; the specific surface area of ​​the positive electrode material is 8.5-15.5 m 2 / g, in some preferred embodiments, 11.35~15.09 g / cm 3 ; The compaction density of the positive electrode material is 2.4~2.85 g / cm 3 , in some preferred embodiments, 2.65-2.73 g / cm 3 .

[0048] 3. The cathode material prepared by the present invention has high capacity retention, good rate performance and high energy density. The capacity retention of the button-type half-cell prepared by the cathode material after 200 cycles at 5.0C rate is 86.5-88.3%. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the SEM image of Example 1.

[0050] Figure 2 This is the SEM image of Example 2.

[0051] Figure 3 This is the SEM image of Comparative Example 4. DETAILED DESCRIPTION

[0052] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0053] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0054] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0055] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0056] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0057] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0058] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0059] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0060]

Positive electrode

[0061] A positive electrode plate includes the positive electrode material of an embodiment of the present invention or the positive electrode material prepared by the preparation method of an embodiment of the present invention.

[0062] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer disposed on at least one surface of the current collector;

[0063] The positive electrode film layer contains the positive electrode material of the embodiment of the present invention or the positive electrode material prepared by the preparation method of the embodiment of the present invention.

[0064] In the above-mentioned “at least one surface of the current collector”, the surface refers to the surface of the current collector perpendicular to the thickness direction of the current collector.

[0065] Exemplarily, the thickness of the positive electrode plate is 0.15 mm to 10 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0066] In some embodiments, the current collector material includes one or more of a carbon material, a metal material, and a carbon fiber composite material.

[0067] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, carbon black, and carbon fiber.

[0068] In some embodiments, the metal material includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, copper, and copper alloy.

[0069] In some embodiments, the positive electrode film layer contains the positive electrode material of the embodiment of the present invention or the positive electrode material prepared by the preparation method of the embodiment of the present invention, and further contains a conductive agent and a binder.

[0070] In some embodiments, the mass ratio of the positive electrode material, the conductive agent, and the binder is not limited to a specific ratio and can be selected according to actual needs; illustratively, the mass ratio can be (60~200): (2~15): (1~15), where it can be 80:10:10. This example is only an example, and the actual ratio is not limited by this mass ratio.

[0071] In some embodiments, the method for preparing a positive electrode film generally includes:

[0072] The positive electrode material, the conductive agent and the binder are dispersed in a solvent and stirred to form a positive electrode slurry;

[0073] The positive electrode slurry is coated on the current collector, and a positive electrode film layer is obtained through steps including drying and cold pressing.

[0074] In some embodiments, the solvent includes N-methylpyrrolidone (NMP), but is not limited thereto.

[0075] In some embodiments, the types and contents of the conductive agent and the binder are not specifically limited and can be selected according to actual needs.

[0076] Exemplarily, the conductive agent includes acetylene black or carbon nanotubes.

[0077] Exemplarily, the binder includes polyvinylidene fluoride (PVDF).

[0078] Exemplarily, the thickness of the positive electrode film layer is 0.1 mm to 8 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.

[0079]

Battery

[0080] A battery comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;

[0081] The positive electrode plate includes the positive electrode plate of the embodiment of the present invention.

[0082] The battery of the embodiment of the present invention has excellent conductivity, cycle stability and rate performance because the positive electrode adopts the positive electrode plate containing the positive electrode material of the embodiment of the present invention or the positive electrode material prepared by the preparation method of the embodiment of the present invention, thereby making the positive electrode of the battery have excellent conductivity, cycle stability and rate performance.

[0083] In some embodiments, the isolation membrane includes one or more of a porous polymer membrane, a non-woven fabric membrane, and an inorganic composite membrane.

[0084] In some embodiments, the material of the porous polymer membrane includes polyethylene (PE) and / or polypropylene (PP).

[0085] In some embodiments, the material of the non-woven fabric separator includes one or more of polyimide (PI), polyester (such as polyethylene terephthalate PET), cellulose, polyamide (PA), and aramid.

[0086] In some embodiments, the nonwoven membrane is a nanofiber nonwoven membrane, including a polyimide nanofiber membrane. In this case, the nanofiber nonwoven membrane has a higher specific surface area and stronger adsorption capacity, and can more effectively isolate the positive and negative electrodes and promote the transmission of lithium ions.

[0087] In some embodiments, the non-woven fabric separator is a ceramic-coated non-woven fabric separator, that is, a ceramic powder (such as Al2O3, SiO2, etc.) is coated on the surface of the non-woven fabric separator (thickness 2μm~15μm). This ceramic-coated non-woven fabric separator not only inherits the high porosity and air permeability of the non-woven fabric, but also increases its thermal stability and mechanical strength.

[0088] In some embodiments, the inorganic composite membrane includes a ceramic-coated composite membrane and an inorganic-organic composite membrane;

[0089] Among them, the ceramic-coated composite membrane is a polymer membrane (such as polyethylene PE, polypropylene PP, etc.) coated with one or more layers of ceramic coating; the ceramic coating can significantly improve the thermal stability and chemical stability of the membrane while maintaining the flexibility and mechanical strength of the polymer membrane;

[0090] Inorganic-organic composite membranes are made by combining inorganic materials with polymer materials through blending, copolymerization or lamination. This composite membrane combines the advantages of inorganic materials and polymer materials and has higher comprehensive performance.

[0091] In some embodiments, the isolation film has a thickness of 60 μm to 100 μm.

[0092] In some embodiments, the negative electrode plate is a common battery plate, generally including a current collector and a negative electrode film layer; the negative electrode film layer contains a negative electrode active material, and the specific negative electrode material and content can be selected according to actual needs without limitation. The preparation of the negative electrode film layer is basically the same as that of the positive electrode film layer.

[0093] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. The materials and contents of the electrolyte salt and the solvent are selected according to actual needs and are not limited.

[0094]

application

[0095] An application of a positive electrode material according to an embodiment of the present invention, a positive electrode material prepared by a method for preparing a positive electrode material according to an embodiment of the present invention, a positive electrode plate according to an embodiment of the present invention, or a battery according to an embodiment of the present invention in household appliances, electric vehicles, electric trains, ships, satellites, or energy storage systems.

[0096] The following is explained in conjunction with specific embodiments. The lithium iron phosphate raw material used in the following embodiments and comparative examples comes from Hunan Yuneng New Energy Battery Materials Co., Ltd., and the particle size of the raw material is D50=3μm.

[0097] Example 1

[0098] The preparation method of the positive electrode material of this embodiment is as follows:

[0099] S1. In molar parts, 10 parts of an amino acid (L-glutamic acid) and 34 parts of a quaternary ammonium hydroxide salt (tetrabutylammonium hydroxide) were mixed in 220 parts of water to obtain a first solution;

[0100] S2. In molar parts, 5 parts of tetraalkyl titanate (tetrabutyl titanate) were mixed in 30 parts of ethanol for 2h at a mixing temperature of 45 ° C to obtain a second solution;

[0101] S3. adding the first solution dropwise to the second solution and mixing to obtain a precursor solution;

[0102] S4. The precursor solution was dried at 150°C for 6h, sintered and crystallized at 380°C for 6h, and crushed (the crushed particle size was D50 = 0.75 μm) to obtain amino acid chelated titanium;

[0103] S5. By molar parts, the amino acid chelated titanium, 20 parts of diisobutylaluminum acetylacetonate complex and lithium iron phosphate were mixed, the molar ratio of amino acid chelated titanium and lithium iron phosphate was 1:7.1, calcined at 850 ° C for 4h, the annealing temperature was set to 500 ° C, and kept at this temperature for 1.5h, cooled to obtain a positive electrode material, the SEM image of the positive electrode material of this embodiment is shown Figure 1 .

[0104] Example 2

[0105] The difference between this embodiment and embodiment 1 is that:

[0106] S1. In molar parts, 10 parts of an amino acid (L-arginine) and 28 parts of a quaternary ammonium hydroxide salt (tetraethylammonium hydroxide) are mixed in 170 parts of water to obtain a first solution.

[0107] The SEM image of the positive electrode material of this embodiment is shown in Figure 2 .

[0108] Example 3

[0109] The difference between this embodiment and embodiment 1 is that:

[0110] The tetraalkyl titanate used in S2 is tetraisopropyl titanate.

[0111] Example 4

[0112] The difference between this embodiment and embodiment 1 is that:

[0113] In S4, the sintering and crystallization are carried out at 350°C for 8 hours, and the crushed particle size is D50 = 0.7 μm.

[0114] Example 5

[0115] The difference between this embodiment and embodiment 1 is that:

[0116] In S5, the molar ratio of amino acid chelated titanium to lithium iron phosphate is 1:6.8.

[0117] Comparative Example 1

[0118] The difference between this comparative example and Example 1 is:

[0119] In S4, the particle size of the pulverized material is D50=0.5 μm.

[0120] Comparative Example 2

[0121] The difference between this comparative example and Example 1 is:

[0122] In S5, the molar ratio of amino acid chelated titanium to lithium iron phosphate is 1:7.9.

[0123] Comparative Example 3

[0124] The difference between this comparative example and Example 1 is:

[0125] In S5, the annealing temperature is 300°C.

[0126] Comparative Example 4

[0127] The difference between this comparative example and Example 1 is:

[0128] In S4, there is no drying operation.

[0129] The SEM image of the positive electrode material of this comparative example is shown in Figure 3 .

[0130] Comparative Example 5

[0131] In S5, no diisobutylaluminum acetylacetonate complex was added.

[0132] The raw materials for preparing the coating layer of this comparative example do not contain diisobutylaluminum acetylacetonate complex.

[0133] Comparative Example 6

[0134] The positive electrode material of this comparative example uses only lithium iron phosphate raw material. The various performance parameters of the positive electrode materials prepared in the above embodiments and comparative examples are shown in Table 1.

[0135]

[0136] The positive electrode materials prepared in the above examples and comparative examples are prepared into button-type half-cells, and the preparation steps are as follows:

[0137] (1) Preparation of positive electrode slurry: According to the mass ratio of positive electrode material: carbon nanotube: polyvinylidene fluoride of 80:10:10, solvent N-methylpyrrolidone (NMP) was added to adjust the viscosity to 4000-8000 mPa·s to prepare positive electrode slurry.

[0138] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sheared to obtain a positive electrode sheet containing a positive electrode film layer.

[0139] (3) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to make a button half-cell.

[0140] The button half-cell was tested in the voltage range of 2.0V-3.8V using Blue Electric equipment, including the discharge capacity at 0.1C, 1.0C and 5.0C, and the capacity retention rate at 5C rate for 200 cycles. The test results are shown in Table 2 below.

[0141]

[0142] As can be seen from Table 2, the particle size of the precursor obtained by crushing Comparative Example 1 is too small, which changes the specific surface area of ​​the positive electrode material and the stacking mode between particles, and ultimately leads to a decrease in the compaction density of the positive electrode material. The reduction in compaction density will directly affect the energy density of the electrode, because a lower compaction density means a reduction in the mass of the material per unit volume, thereby reducing the content of the positive electrode material in the electrode. In addition, a smaller particle size may also lead to an increase in electrode resistance because the contact resistance inside the material is increased. These factors will ultimately affect the cycle life of the battery, because the increase in resistance and the decrease in energy density will accelerate the decay of battery performance.

[0143] In Comparative Example 2, due to the small amount of precursor added, the electrochemical performance is significantly reduced. The insufficient amount of precursor may not provide enough active material, thereby reducing the initial capacity and energy density of the battery. In addition, less precursor may also cause the structure of the electrode material to be unstable, affecting the performance of the battery during long-term cycling.

[0144] In Comparative Example 3, due to the low annealing temperature, the chemical bonds between Ti and Al and nitrogen are difficult to form, which is not conducive to the diffusion channel of lithium ions and the electron transmission path. The lower annealing temperature may lead to insufficient crystallinity of the material, thereby affecting its structural stability and electrochemical activity.

[0145] In Comparative Example 4, the precursor is directly sintered and crystallized without drying, which has a great influence on the morphology and element distribution of the subsequent positive electrode material. Therefore, the drying operation before the precursor is sintered and crystallized is very important. Figure 3 It can be seen from the SEM image in that the positive electrode material obtained under this condition is severely agglomerated and has an uneven particle size distribution, with a significantly larger irregular block structure generated.

[0146] In Comparative Example 5, aluminum ions can be effectively filled into the lithium iron phosphate lattice to increase its discharge capacity and cycle performance. The coating layer does not add diisobutylaluminum acetylacetonate complex, so new lattice defects or vacancies cannot be introduced to promote ion diffusion, and therefore lithium ion transmission cannot be promoted.

[0147] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: It includes a core and a cladding layer; The core is lithium iron phosphate; The raw materials for preparing the coating layer include amino acid chelated titanium and diisobutylaluminum acetylacetonate complex; The amino acid chelated titanium preparation raw materials include the following preparation raw materials in molar proportions: 10 parts of amino acid, 20-50 parts of quaternary ammonium hydroxide salt, 3-8 parts of tetraalkyl titanate and 30-60 parts of ethanol; The amino acid is L-glutamic acid or L-arginine; The tetraalkyl titanate is tetrabutyl titanate or tetraisopropyl titanate; The quaternary ammonium hydroxide salt is at least one of tetrabutylammonium hydroxide, tetraethylammonium hydroxide and dimethyldiethylammonium hydroxide; The preparation method of the positive electrode material comprises: mixing amino acid chelated titanium, diisobutylaluminum acetylacetonate complex and lithium iron phosphate, calcining and annealing to obtain the positive electrode material; Wherein, the calcination temperature is 700-900°C, and the calcination time is 2-5h; The annealing temperature is 500-600° C., and the annealing temperature is maintained for 1-2.5 hours.

2. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following conditions (1) to (2): (1) The molar ratio of the amino acid chelated titanium to the lithium iron phosphate is 1:6.5-7.5; (2) The molar ratio of the tetraalkyl titanate to the diisobutylaluminum acetylacetonate complex is 1:3-5.

3. The positive electrode material according to claim 1, characterized in that Satisfy at least one of the following conditions (1) to (3): (1) The powder resistivity of the positive electrode material is 6.5-15 Ω·cm; (2) The specific surface area of ​​the positive electrode material is 8.5~15.5 m 2 / g; (3) The compaction density of the positive electrode material is 2.40~2.85 g / cm 3 .

4. A method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Mixing an amino acid and a quaternary ammonium hydroxide salt in water to obtain a first solution; S2. The tetraalkyl titanate is mixed in ethanol to obtain a second solution; S3. adding the first solution dropwise to the second solution and mixing to obtain a precursor solution; S4. The precursor solution is dried, sintered, crystallized, and crushed to obtain amino acid chelated titanium; S5. Mix amino acid chelated titanium, diisobutylaluminum acetylacetonate complex and lithium iron phosphate, calcine and anneal to obtain a positive electrode material.

5. The method for preparing the positive electrode material according to claim 4, characterized in that S2 satisfies at least one of the following conditions (1) to (2): (1) The mixing temperature is 40-50°C; (2) The mixing time is 2 to 5 hours.

6. The method for preparing the positive electrode material according to claim 4, characterized in that S4 satisfies at least one of the following conditions (1) to (5): (1) The drying time is 2 to 8 hours; (2) The drying temperature is 100-170°C; (3) The sintering crystallization temperature is 300-400°C; (4) The sintering and crystallization time is 5 to 8 hours; (5) The particle size of the crushed material is D50 = 0.7 ~ 0.85 μm.

7. A battery comprising a positive electrode, a separator, a negative electrode and an electrolyte, characterized in that: The positive electrode plate comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the preparation method of the positive electrode material according to any one of claims 4 to 6.

8. Use of the battery as claimed in claim 7 in household appliances, electric bicycles, electric vehicles, electric trains, ships, satellites or power grid energy storage systems.